Platelet function tests and inflammatory markers for the differentiation of primary thrombocytosis and secondary thrombocytosis - Piyapong Kanya (2019)
© 2019 Asian Pacific Journal of Cancer Prevention. Background: The prognosis and management of primary thrombocytosis (PT) and secondary thrombocytosis (ST) are different. This study aims to evaluate the role of platelet function tests by light transmission platelet aggregometry (LTA), plasma von Willebrand factor antigen (vWF:Ag), ristocetin cofactor activity (vWF:RCo) and inflammatory markers [erythrocyte sedimentation rate (ESR), C-reactive protein (CRP)] for the differentiation between PT and ST. Methods: This prospective study was carried out in patients with platelet counts greater than 450 x 109/L. Primary outcomes were the sensitivity and specificity of platelet function tests by LTA for the differentiation of PT and ST. Secondary outcomes were sensitivity and specificity of ESR, CRP, vWF:Ag, and vWF:RCo for the differentiation of PT and ST. Results: Fifty-two patients were enrolled onto the study of which 26 (50%) had PT. The sensitivity and specificity of epinephrine, collagen, and arachidonic acid (AA) induced abnormal LTA for the differentiation of PT from ST were sensitivity of 50%, 38.5%, 26.9% and specificity of 88.5%, 100%, 100% respectively. The sensitivity and specificity of abnormal ESR, CRP, and either abnormal ESR or CRP in the differentiation of ST from PT were sensitivity of 88.5%, 80.8%, 100% and specificity of 65.4%, 61.5%, 46.2% respectively. The sensitivity and specificity of low vWF:Ag and vWF:RCo in the differentiation of PT from ST were sensitivity of 7.69%, 42.3% and specificity of 100%, 88.5% respectively. Conclusions: Abnormal platelet function determined by LTA with collagen, AA, epinephrine had high specificity ratings enabling the differentiation between PT and ST. vWF:RCo, ESR and CRP levels could be helpful in differentiating between PT and ST.